Comparative efficacy of first-line natalizumab vs IFN-β or glatiramer acetate in relapsing MS. Issue 2 (April 2016) - Spelman, Tim; Kalincik, Tomas; Jokubaitis, Vilija; Zhang, Annie; Pellegrini, Fabio; Wiendl, Heinz; Belachew, Shibeshih; Hyde, Robert; Verheul, Freek; Lugaresi, Alessandra; Havrdová, Eva; Horáková, Dana; et al.
Abstract: Background: We compared efficacy and treatment persistence in treatment-naive patients with relapsing-remitting multiple sclerosis (RRMS) initiating natalizumab compared with interferon-β (IFN-β)/glatiramer acetate (GA) therapies, using propensity score–matched cohorts from observational multiple sclerosis registries. Methods: The study population initiated IFN-β/GA in the MSBase Registry or natalizumab in the Tysabri Observational Program, had ≥3 months of on-treatment follow-up, and had active RRMS, defined as ≥1 gadolinium-enhancing lesion on cerebral MRI at baseline or ≥1 relapse within the 12 months prior to baseline. Baseline demographics and disease characteristics were balanced between propensity-matched groups. Annualized relapse rate (ARR), time to first relapse, treatment persistence, and disability outcomes were compared between matched treatment arms in the total population (n = 366/group) and subgroups with higher baseline disease activity. Results: First-line natalizumab was associated with a 68% relative reduction in ARR from a mean (SD) of 0.63 (0.92) on IFN-β/GA to 0.20 (0.63) ( p [signed-rank] < 0.0001), a 64% reduction in the rate of first relapse (hazard ratio [HR] 0.36, 95% confidence interval [CI] 0.28–0.47; p < 0.001), and a 27% reduction in the rate of discontinuation (HR 0.73, 95% CI 0.58–0.93; p = 0.01), compared with first-line IFN-β/GA therapy. Confirmed disability progression and area under the Expanded Disability Status Scale–time curve analyses were not significant. Similar relapse and treatment persistence results were observed in each of the higher disease activity subgroups. Conclusions: This study provides Class IV evidence that first-line natalizumab for RRMS improves relapse and treatment persistence outcomes compared to first-line IFN-β/GA. This needs to be balanced against the risk of progressive multifocal leukoencephalopathy in natalizumab-treated patients. Classification of evidence: This study provides Class IV evidence that first-line natalizumab for RRMS improves relapse rates and treatment persistence outcomes compared to first-line IFN-β/GA.